(untitled) (Journal of Architectural Design, 2022)
The paper shows the place and importance of the computer in the calculation of problems in mechanics and mathematical modeling. Basic information on the use of differential and integral models of the relationship between stress and strain in problems of the theory of viscoelasticity is given. Using the example of free vibrations of viscoelastic plates with and without taking into account the notch, the main stages of solving this problem are given